The Water to Solute Permeability Ratio Governs the Osmotic Volume Dynamics in Beetroot Vacuoles - Vitali, Victoria; Sutka, Moira; Amodeo, Gabriela; Chara, Osvaldo; Ozu, Marcelo (Frontiers in Plant Science, 2016)
Plant cell vacuoles occupy up to 90% of the cell volume and, beyond their physiological function, are constantly subjected to water and solute exchange. The osmotic flow and vacuole volume dynamics relies on the vacuole membrane -the tonoplast- and its capacity to regulate its permeability to both water and solutes. The osmotic permeability coefficient (Pf) is the parameter that better characterizes the water transport when submitted to an osmotic gradient. Usually, Pf determinations are made in vitro from the initial rate of volume change, when a fast (almost instantaneous) osmolality change occurs. When aquaporins are present, it is accepted that initial volume changes are only due to water movements. However, in living cells osmotic changes are not necessarily abrupt but gradually imposed. Under these conditions, water flux might not be the only relevant driving force shaping the vacuole volume response. In this study, we quantitatively investigated volume dynamics of isolated Beta vulgaris root vacuoles under progressively applied osmotic gradients at different pH, a condition that modifies the tonoplast Pf. We followed the vacuole volume changes while simultaneously determining the external osmolality time-courses and analyzing these data with mathematical modelling. Our findings indicate that vacuole volume changes, under progressively applied osmotic gradients, would not depend on the membrane elastic properties, nor on the non-osmotic volume of the vacuole, but on water and solute fluxes across the tonoplast. We found that the volume of the vacuole at the steady state is determined by the ratio of water to solute permeabilites (Pf/Ps), which in turn is ruled by pH. The dependence of the permeability ratio on pH can be interpreted in terms of the degree of aquaporin inhibition and the consequently solute transport modulation. This is relevant in many plant organs such as root, leaves, cotyledons or stems that perform extensive rhythmic growth movements, which very likely involve considerable cell volume changes within seconds to hours.